KODLAMA EĞİTİMİNDE OYUN GELİŞTİRME PLATFORMLARININ KULLANIMI. - YILMAZ İNCE, Ebru (Mehmet Akif Ersoy University Journal of Education Faculty)
The development and operation of technological products are provided by computer software. Giving high quality software training to individuals ensures that our country develops technologically. Software development process may require a long time. It is also necessary for programmers to have certain technical skills. Therefore, it is very important that the motivation of software development of students is kept high. Increasing the quality of coding training can be achieved by encouraging students to code in the areas that are relevant. Computer games are software that digital generation uses for entertainment purposes in their leisure time. Today, various computer game development platforms are being used for the development of computer games. The curriculum of the game programming course is required to improve the game through coding by the students. In this research, the opinions of the students regarding the use of game platforms in coding training are invesgitaged. The study is designed as a holistic single-case study from the qualitative research type. Data Suleyman Demirel University Vocational Computer Programming Program has been collected by students taking game programming course using semi-structured interview method. Interviews are analyzed by content analysis method. At the end of the research, students' opinions about game programming lesson are described.